Desenvolvimento de aplicativo de tecnologia móvel para arborização urbana - Ramos, Rafael Rieger (2017)
The increasing development of the urban areas in the country turns the search for environmental and esthetic improvements to the cities the major key in the urban forestation planning. The precision forestry emerges as an urban afforestation and urban centers plan ally, offering control and scheduling activities such as the implantation and management of the vegetation in public routes, gardens and parks. Aiming to assist the urban forestation planning, the C7 Lignum Urben application was developed, which is a mobile tool linked to smartphones and tablets Android System that plans the urban forestation by the registration and evaluation of copies, the implantation and management of the vegetation in public areas and the emission of reports that allows group decisions. The C7 Lignum Urben provides more agility in the processes of data retrieval and dissemination due to the ability to specialize data and send reports in .CSV and .PDF formats that can be edited and take up less space.